4, 300 steps per day prior to surgery are associated with improved outcomes after pancreatectomy. Issue 1 (January 2023) - Cos, Heidy; Zárate Rodríguez, Jorge G.; Srivastava, Rohit; Bewley, Alice; Raper, Lacey; Li, Dingwen; Dai, Ruixuan; Williams, Gregory A.; Fields, Ryan C.; Hawkins, William G.; Lu, Chenyang; Sanford, Dominic E.; et al.
Abstract: Background: Decreased preoperative physical fitness and low physical activity have been associated with preoperative functional reserve and surgical complications. We sought to evaluate daily step count as a measure of physical activity and its relationship with post-pancreatectomy outcomes. Methods: Patients undergoing pancreatectomy were given a remote telemonitoring device to measure their preoperative levels of physical activity. Patient activity, demographics, and perioperative outcomes were collected and compared in univariate and multivariate logistic regression analysis. Results: 73 patients were included. 45 (61.6%) patients developed complications, with 17 (23.3%) of those patients developing severe complications. These patients walked 3437.8 (SD 1976.7) average daily steps, compared to 5918.8 (SD 2851.1) in patients without severe complications (p < 0.001). In logistic regression analysis, patients who walked less than 4274.5 steps had significantly higher odds of severe complications (OR = 7.5 (CI 2.1, 26.8), p = 0.002). Conclusion: Average daily steps below 4274.5 before surgery are associated with severe complications after pancreatectomy. Preoperative physical activity levels may represent a modifiable target for prehabilitation protocols.